العنف في المؤسسة التربوية هل هو خلل في وظيفة مؤسسات التنشئة أم لا توافق مؤسسي - نبيل, حميدشة (Changement Social, 2019)
لقد لازم العنف الإنسان مند وجوده على الأرض، فالعنف كظاهرة اجتماعية و إنسانية بدأت ممارسته من طرف ابني آدم عليه السلام، ومنذ ذلك الحين أخد أشكالا عدة، بدءا بالعنف المادي وانتهاء بالعنف الرمزي، كما اتخذ أنواعا عدة أيضا كالعنف السياسي وهو العنف الممارس  للحصول على السلطة أو الإبقاء عليها و العنف الاقتصادي كالاحتكار والمضاربة و غيرها إضافة إلى العنف الديني والعنف التربوي وغيرها من الأنواع. كما تعددت أسبابه في المجتمع الواحد وفي مختلف المجتمعات على اختلاف ثقافاتها و نظمها المجتمعية. ومنه سنحاول في هذه الورقة البحثية أن نتناول العنف التربوي وخاصة العنف الممارس في المؤسسات التربوية. من حيث أشكاله وأسبابه و آليات الحد منه. وسنركز على ما إذا كان هذا العنف هو خلل في وظيفة القائمين على العملية التربوية، أم هو لا توافق بين الفرد والمؤسسة التربوية نتيجة التشريعات والقوانين الناظمة للعملية التربوية، أم هو ناتج عن عدم التساند الوظيفي بين مختلف المؤسسات التربوية. سنعرض مساهمات بعض الدول في محاربة ظاهرة العنف في المؤسسات التربوية. Violence has been human since its existence on the ground. Violence is a social and human phenomenon that has been practiced by the sons of Adam, peace be upon him. Since then, he has taken many forms, starting with physical violence and ending with symbolic violence. To obtain or maintain power and economic violence such as monopolization, speculation, etc., in addition to religious violence, educational violence and other kinds. As well as many reasons in one society and in different societies with different cultures and community systems. In this paper we will attempt to address the educational violence, especially the violence practiced in educational institutions. In terms of its forms, causes and mechanisms of reduction. And we will focus on whether this violence is a defect in the function of those responsible for the educational process, or does not agree between the individual and the educational institution as a result of legislation and laws governing the educational process, or is the result of lack of support between the various educational institutions. We will present the contributions of some countries in combating violence in educational institutions the status of anthropology in the world.